Determinants of the influence of voters and interest groups on the political decision making process - Ivo Bischoff (Justus-Liebig-Universität Gießen, Fachbereich Wirtschaftswissenschaften, 2001)
This paper provides a comprehensive theoretical model of the political decision making process. Therein two ideologically different political parties compete for power. Their primary instrument in this competition are programmatic concessions in favor of voters and interest groups. As any concession causes losses in utility for the party members, the parties try to win the election with as little concessions as possible. The efficient amount of concessions and their distribution on different groups of voters and interest groups is derived. These concessions are taken as an indicator for the influence of these two groups of political agents on the political decision making process. Hence the political model developed in this paper helps to determine the political influence of voters and interest groups. The illustrations show that the efficient amount of concessions depends on the closeness of the election race. The closer the initial distribution of votes, the more concessions can voters and interest groups wring from the political parties. The characteristics of the political landscape, e.g. the share of informed voters and the degree of ideological polarization, are found to determine the efficient amount of concessions and thus the influence of voters and interest groups on the political decision making process.
Keywords: D72; 330; Public Choice; theory; voters; interest groups; election; Ökonomische Theorie der Demokratie; Parteiprogramm; Wahlverhalten; Interessenvertretung; Public Choice; Theorie